Differentiability of integrals of real functions with respect to L_0-valued measures - Radchenko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain conditions for the convergence of expressions (μ (A))^ - 1 _A fdμ in L_0 as the set A decreases.